Answer:
FG = 39
Explanation:
From the question given:
FH = 9x + 15
GH = 5x + 4
FG = ?
From the question given above, we can say that G is the midpoint of FH. This implies that:
FH = FG + GH
With the above idea in mind, we can obtain FG as follow:
FH = 9x + 15
GH = 5x + 4
FG = ?
FH = FG + GH
9x + 15 = FG + 5x + 4
Rearrange
FG = 9x + 15 - 5x - 4
FG = 9x - 5x + 15 - 4
FG = 4x + 11
Next, we shall determine the value of x. This can be obtained as follow:
Since G is the midpoint of FH, it therefore means that FG and GH are equal i.e
FG = GH
With the above idea in mind, we can obtain the value of x as follow:
FG = 4x + 11
GH = 5x + 4
FG = GH
4x + 11 = 5x + 4
Collect like terms
11 - 4 = 5x - 4
7 = x
x = 7
Thus, we can obtain the value of FG as follow:
FG = 4x + 11
x = 7
FG = 4x + 11
FG = 4(7) + 11
FG = 28 + 11
FG = 39
***Check ***
FH = 9x + 15
x = 7
FH = 9(7) + 15 = 63 + 15 = 78
GH = 5x + 4
x = 7
GH = 5(7) + 4 = 35 + 4 = 39
FG = 4x + 11
x = 7
FG = 4(7) + 11 = 28 + 11 = 39
FH = FG + GH
FH = 78
FG = 39
GH = 39
FH = FG + GH
78 = 39 + 39
78 = 78